Food, Agriculture and Natural Resources Policy: Stakeholder Directory 2010 - Takavarasha, Tobias (FANRPAN, 2010)
This Directory is intended to bring together the network's stakeholders. The list is drawn from all engagements with the network through meetings and other modes of communication. Users are encouraged to use this directory to assist in communicating among themselves in-country, regionally and globally.